2021
DOI: 10.3390/ijms22041885
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Kinase Inhibition in Ischemic Factor Modeling In Vitro

Abstract: The contribution of many neuronal kinases to the adaptation of nerve cells to ischemic damage and their effect on functional neural network activity has not yet been studied. The aim of this work is to study the role of the four kinases belonging to different metabolic cascades (SRC, Ikkb, eEF2K, and FLT4) in the adaptive potential of the neuron-glial network for modeling the key factors of ischemic damage. We carried out a comprehensive study on the effects of kinases blockade on the viability and network fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…It was shown that at 21 DIV 59.28 ± 6.05% of cells in the hippocampal cell culture were active, the duration of calcium oscillations was 12.37 ± 1.16 s, and the frequency was 1.34 ± 0.14 osc/min ( Figure 2 A–C). Exposure to both ischemic factors leads to the inhibition of calcium activity and a significant decrease in the number of cells in which Ca 2+ events are registered (GD—41.62 ± 1.71,%; Hypoxia—35.91 ± 1.05%) and is consistent with previously published data [ 17 ]. The duration and frequency of calcium oscillations in modeling glucose deprivation and hypoxia did not change significantly.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It was shown that at 21 DIV 59.28 ± 6.05% of cells in the hippocampal cell culture were active, the duration of calcium oscillations was 12.37 ± 1.16 s, and the frequency was 1.34 ± 0.14 osc/min ( Figure 2 A–C). Exposure to both ischemic factors leads to the inhibition of calcium activity and a significant decrease in the number of cells in which Ca 2+ events are registered (GD—41.62 ± 1.71,%; Hypoxia—35.91 ± 1.05%) and is consistent with previously published data [ 17 ]. The duration and frequency of calcium oscillations in modeling glucose deprivation and hypoxia did not change significantly.…”
Section: Resultssupporting
confidence: 92%
“…To assess the viability of primary cultures, 7 days after modeling stress factors, cells were stained in vitro with specific fluorescent dyes: propidium iodide (Sigma Aldrich, St. Louis, MO, USA) and bisbenzimide (Sigma Aldrich, St. Louis, MO, USA), which allow visualizing the nuclei of dead cells and the total number of cells in the culture, respectively [ 17 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that primary hippocampal cultures can serve as a relevant biological model of the brain neuron-glial networks in vitro [ 24 ]. In particular, we characterized the cellular content and the features of functional activity of neuron-glial networks in the different period of cultivation in vitro [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%